Cutaneous crospovidone reaction secondary to subcutaneous injection of buprenorphine. (15th December 2019) - Marka, Arthur; Hoyt, Brian S.; Dagrosa, Alicia T.; Barton, Dorothea T.; Kim, Andrew; Linos, Konstantinos; Yan, Shaofeng
Abstract: Crospovidone is an insoluble pharmaceutical disintegrant that has been implicated in a rare foreign body reaction in injection drug users, classically associated with pulmonary angiothrombosis. We recently reported the first known cases of cutaneous crospovidone deposition. We herein report two additional cases with unique clinicopathologic manifestations, both in the setting of suspected injection drug abuse. Additionally, we provide a comprehensive overview of the distinct histomorphology and reproducible histochemistry of crospovidone.